The prevalence of multidrug resistance in Staphylococcus hominis isolated from clinical materials - Magdalena Szemraj; Paulina Glajzner; Kamila Olszowiec; Monika Sienkiewicz (Scientific Reports)
Abstract The treatment of infections caused by Staphylococcus hominis remains a challenge, mainly due to the increasing resistance of these bacteria to antibiotics. The aim of the study was to determine antibiotic resistance in 62 strains S. hominis isolated from clinical materials, and to identify the molecular basis of resistance to antibiotics. Forty-six strains were both methicillin-resistant and harbored the mecA gene. Twenty-three of these strains had mec complex A and ccr complex AB1. Such a combination of the mec and ccr complexes does not correspond to any cassettes that have been demonstrated so far. However, over 80% of the tested strains were multidrug-resistant, of which as many as 12 were resistant to at least seven antibiotics. More than a half of strains harbored the tetK, acc(6’)-Ie aph(2’’), and ant(4’)-I genes. erm(C) was the most common resistant gene to antibiotics from the MLS group. Two strains had as many as five antibiotic resistance genes from the tested groups (erm(C), msr(A), msr(B), mph(C), lnu(A)). The presence of the vga gene encoding resistance to streptogramins A was detected in one strain. All of strains were sensitive to vancomycin. However, 11 of them had reduced sensitivity to this antibiotic and eight of them were characterized by a heterogeneous resistance profile to this antibiotic. Our results clearly shows increasing threat of S. hominis caused by their multi-resistance. Moreover, these bacteria can constitute a reservoir of resistance genes for more pathogenic bacteria.